2012
DOI: 10.1152/jn.00094.2012
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine produces bidirectional, concentration-dependent effects on dopamine neuron excitability and dopamine-mediated synaptic currents

Abstract: Amphetamine-like compounds are commonly used to enhance cognition and to treat attention deficit/hyperactivity disorder, but they also function as positive reinforcers and are self-administered at doses far exceeding clinical relevance. Many of these compounds (including methamphetamine) are substrates for dopamine reuptake transporters, elevating extracellular dopamine by inhibiting uptake and promoting reverse transport. This produces an increase in extracellular dopamine that inhibits dopamine neuron firing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 38 publications
12
87
0
Order By: Relevance
“…BK channels are involved in AP repolarization in several neuronal types (Adams et al, 1982;Lancaster and Nicoll, 1987;Storm, 1990;Lin et al, 2014). Consistent with these reports, we found BK channels are expressed in dopamine neurons (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…BK channels are involved in AP repolarization in several neuronal types (Adams et al, 1982;Lancaster and Nicoll, 1987;Storm, 1990;Lin et al, 2014). Consistent with these reports, we found BK channels are expressed in dopamine neurons (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, METH exposure broadened the spike halfwidth measured at the half-maximal voltage (Fig. 1 D METH and paxilline blockade of BK channels regulate the repolarization and AHP of APs Activation of BK channels has been shown to contribute to AP repolarization and AHP (Adams et al, 1982;Lancaster and Nicoll, 1987;Faber and Sah, 2002;Lin et al, 2014). Thus, to understand whether METH regulation of intrinsic firing behavior of dopamine neurons involves BK channel activity, we examined the influence of METH and a BK channel blocker paxilline on single spike amplitudes, repolarization, and AHP in spontaneously active dopamine neurons (Fig.…”
Section: Identification Of Dopamine Neuronsmentioning
confidence: 97%
“…As expected from the actions of methamphetamine or COC (61,63), the amplitude, time to peak, and duration of evoked D2R-mediated IPSCs in WT slices treated with AMPH increased significantly relative to no-drug conditions and remained elevated throughout the AMPH application. However, the AMPH-induced increase in D2R-mediated IPSC amplitude was blunted in DAT Val559 slices (Fig.…”
Section: Da Neurons From Dat Val559 Mice Display Alterations In Basalsupporting
confidence: 58%
“…5). Recently, it has become clear that, aside from these traditional mechanisms, amphetamines are also capable of modulating action potential-dependent neurotransmitter release (Branch and Beckstead, 2012;Daberkow et al, 2013). Furthermore, amphetamines regulate DA neurotransmission via inhibition of monoamine oxidase (MAO) and enhancement of tyrosine hydroxylase (TH) and have numerous other receptor targets, including the a2-adrenergic receptor, the sigma receptor, and the trace amine-associated receptor 1 (TA 1 ) receptor (Fung and Uretsky, 1982;Robinson, 1985;Ritz and Kuhar, 1989;Matsumoto et al, 2014;Reese et al, 2014).…”
Section: B Amphetamine-type Psychostimulantsmentioning
confidence: 99%
“…Unlike AMPH, MPH was recently shown to decrease exocytotic DA release (Federici et al, 2014), which may help explain the differing subjective effects of this drug. The exact mechanism by which AMPH increases the exocytotic release of DA is unknown, but may be related to the ability of AMPH to induce persistent transporter-mediated ionleakage and excitatory conductance (Ingram et al, 2002;Branch and Beckstead, 2012;Rodriguez-Menchaca et al, 2012). It has been suggested that reuptake inhibition is primarily associated with lower drug concentrations, possibly corresponding to those in the therapeutic range, whereas doses in the recreational range shift the importance to AMPH-mediated DA release (Calipari and Ferris, 2013).…”
Section: Comparison Of the Mechanisms Of Action Of Amphetamine Versusmentioning
confidence: 99%